Natural Products and Retinal Ganglion Cells: Protective Roles of Edible Wild Vegetables Against Oxidative Stress in Retinal Ganglion Cells - Jung, S.H. (Elsevier Inc., 2014)
Progressive degeneration and death of retinal ganglion cells (RGCs) is a major risk factor for glaucoma. Increased intraocular pressure (IOP) is also known as a major risk factor and an underlying mechanism in the pathogenesis of glaucoma. Therefore, reduction of IOP is a primary target in glaucoma treatment. However, alternative approaches are needed because reduction of IOP is not always effective in patients with glaucoma (e.g., normal-tension glaucoma). One possible way to prevent or treat glaucoma is to protect RGCs by inhibiting the apoptotic cascade. Oxidative stress also plays an important role in the pathogenesis of glaucoma, and natural products such as natural antioxidants may be putative substances for preventing and treating glaucoma via neuroprotection of RGCs. This chapter summarizes the available data on natural products with potential neuroprotective effects for RGCs, and discusses the use of edible wild vegetables, which may have a role in the prevention of glaucoma by inhibiting the overproduction of reactive oxygen species. ？ 2014 Elsevier Inc. All rights reserved.